Passive Optical Communications Module for the Internet of Things - Ribeiro, Tiago (2018)
The Internet of Things (IoT) promotes interconnectivity between devices and these keep appearing in larger quantities throughout the years, with the evolution of communication technologies. However, scalability comes with a price, since for a higher quantity of devices comes the need for better transmission channels, with higher reach, availability and improved security capabilities. The infrastructure that comes with this ubiquitous network is very expensive so there is a need for finding low-cost solutions for the transmission of data, benefiting from the qualities of the optical fibers.Wireless technologies already provide a way to solve these issues, but the use of optical fibers would give to the IoT their own unique features, such as high bandwidth, long reach, signal integrity and high security. But IoT devices should not be power hungry nor have very limiting electrical-to-optical conversions, so a passive optical communications module based of fiber Bragg gratings for long reach and for the upload of information with low data rates should be implemented. This module would be integrated in the IoT ecosystem by connecting it to the existent dark fibers all over the world.A simulator of this module was implemented, capable of reproducing its characteristics for the transmission of information modulated in Frequency-Shift Keying and On-Off Keying modulation schemes. The study of the system performance for these schemes was made by estimating the Bit Error Rate using the Error Vector Magnitude metric, in relation to the received optical power.